Neutralizing capacity of a new monovalent anti-Bothrops atrox antivenom: comparison with two commercial antivenoms (1997)
ABSTRACT: Three horse-derived antivenoms were tested for their ability to neu-tralize lethal, hemorrhagic, edema-forming, defibrinating and myotoxicactivitiesinduced by the venom of Bothrops atrox from Antioquia andChocó (Colombia). The following antivenoms were used: a) polyva-lent (crotaline) antivenom produced by Instituto Clodomiro Picado(Costa Rica), b) monovalent antibothropic antivenom produced byInstituto Nacional de Salud-INS (Bogotá), and c) a new monovalentanti-B. atrox antivenom produced with the venom of B. atrox fromAntioquia and Chocó. The three antivenoms neutralized alltoxicactivitiestested albeit with different potencies. The new monovalentanti-B. atrox antivenomshowed the highest neutralizing ability againstedema-forming and defibrinating effects of B. atrox venom (41 ± 2and 100 ± 32 μl antivenom/mgvenom, respectively), suggesting thatitshould be usefulin the treatment of B. atrox envenomation inAntioquia and Chocó.